Programming Microsoft Azure Service Fabric - Bai, Haishi (Microsoft Press : Pearson Education, 2018)
This book combines a comprehensive guide to success with Microsoft Azure Service Fabric and a practical catalogue of design patterns and best practices for microservices design, implementation, and operation. Haishi Bai brings together all the information you'll need to deliver scalable and reliable distributed microservices applications on Service Fabric. He thoroughly covers the crucial DevOps aspects of utilising Service Fabric, reviews its interactions with key cloud-based services, and introduces essential service integration mechanisms such as messaging systems and reactive systems. Lead.